1991
DOI: 10.1007/bf01709656
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor (G-CSF) treatment in a neutropenic leukemia patient with diffuse interstitial pulmonary infiltrates

Abstract: Adult respiratory distress syndrome (ARDS) in patients suffering from acute leukemia usually occurs during chemotherapy-induced neutropenia. In addition, intensified chemotherapy with high-dose cytosine arabinoside and mediastinal irradiation may contribute to the development of ARDS. This complication is usually refractory to conservative treatment with antibiotics, steroids, and mechanical ventilation. In this report, we describe a 25-year-old patient with acute lymphoblastic leukemia who developed ARDS duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This suggested that early and steep recovery of neutrophil counts following severe neutropenia contributed to the development of pulmonary interstitial infiltration and possibly ARDS. In contrast, other authors [10, 19, 20, 21, 22]noted that ARDS was likely to occur during neutropenia. Apart from the complement-neutrophil pathway, they assumed that other mediators of the inflammatory pathway play important roles in the development of ARDS [22, 23].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This suggested that early and steep recovery of neutrophil counts following severe neutropenia contributed to the development of pulmonary interstitial infiltration and possibly ARDS. In contrast, other authors [10, 19, 20, 21, 22]noted that ARDS was likely to occur during neutropenia. Apart from the complement-neutrophil pathway, they assumed that other mediators of the inflammatory pathway play important roles in the development of ARDS [22, 23].…”
Section: Discussionmentioning
confidence: 53%
“…Similarly, Heyll et al [10]reported an incidence of ARDS of 11% in patients with acute leukemia who received chemotherapy without G-CSF. Consequently the incidence of ARDS in our department was regarded as common.…”
Section: Discussionmentioning
confidence: 99%
“…In its attempt to activate or increase the neutrophil count, G‐CSF perhaps contributes to the development of ARDS [5, 6]. There have been cases of ARDS or interstitial pneumonia associated with G‐CSF [5, 7–11]; there have also been cases where ARDS improved whilst G‐CSF was being given and the neutrophil count was increasing [12]. In cases of neutropenia where pulmonary infection coexisted with the use of G‐CSF, ARDS seemed to worsen [5].…”
Section: Discussionmentioning
confidence: 99%
“…Although rhG-CSF may exert a potential negative effect on the course of ARDS by activating neutrophils leading to the release of some mediators, the application of rhG-CSF was an effective therapeutic approach for preventing the fatal outcome of ARDS. Whilst neutrophil depletion prevents lung injury in a variety of intact animal models [23], HEYLL et al [24] reported that administration of rhG-CSF resulted in a successful outcome in a neutropenic leukaemia patient with ARDS. KOIZUMI et al [25] reported that G-CSF, in spite of the increase in peripheral neutrophil count, did not aggravate lung injury induced by endotoxin in a sheep model.…”
Section: Discussionmentioning
confidence: 99%